Financial and Strategic Benefits of Mergers and Acquisitions in Machinery, equipment, furniture, and recycling sector of the UK - Wang, Yuanya (2013)
This paper mainly examines the post-acquisition financial performance of acquiring firms (combined firms) in machinery, equipment, furniture and recycling sector of UK completed in 2008- 2009. Through reviewing historical studies, I also make theoretical analysis and obtain empirical evidence on the role of managerial issues during the takeovers process. Since this study does not try to include every possible factor, I will select several major ones as variables in regression model. For other perspectives that may have impact on takeover consequences, this paper will also briefly discuss them in related parts. First, empirical evidence on managerial aspect demonstrates a surprising phenomenon that managerial improvement after a takeover is not as unambiguous as we initially expected. Undoubtly, managers’ personality could substantially affect post-takeover performance. Many of cases, unfortunately, discover that managers’ overconfidence frequently reduce firms’ efficiency and takeover synergies, though they pursue maximizing firms’ benefits rather than their own. The results of panel data analysis of all chosen firms suggest that MA activities have no direct impact on firm performance since the parameter of dummy variable MA is very close to zero. According to the regression tables, benchmark firms outperform MA firms after deals, indicating that MA activities could negatively affect operating performance through other immeasurable factors. In addition, regression containing all sample firms shows that the selected independent variables have no influence on the dependent variable (profitability), except for pre-performance impact. After grouping MA firms into two categories, the statistical analysis indicates that explanatory variables gradually display clear relations with profitability. In conclusion, managers should be cautious to MA activities as empirical studies provide substantial evidence on post-merger performance decay.